Pesantren Tegalsari: Antara Eksistensi dan Dekadensi: Tegalsari Islamic Boarding School: Between Existence and Decadence - Shiddiq, Mohammad Alwi (Journal of Islamic History, 2022)
Discussions related to pesantren are always interesting to discuss because they are old institutions of Islamic religious education. There are many things that can be studied, starting from the teaching, the life of the pesantren, the role of the kiai, to the santri. This paper aims to find out the Pesantren Tegalsari and Kiai Hasan Besari, describe the Pesantren Tegalsari after Kiai Hasan Besari, and find out the condition of the pesantren after Kiai Hasan Besari. This research is a library research with the research method used is the historical method. The results of this study indicate that discussing the Pesantren Tegalsari is incomplete without Kiai Hasan Besari who was able to bring the existence of Tegalsari in the mid-19th century into progress, after Kiai Hasan Besari from 1862 to 1964 M there were eight successor kiai who were considered to be experiencing decadence, and in the period there are causative factors, changing aspects, and impacts from within Tegalsari itself and from outside. The Tegalsari environment is currently a religious tourism destination. pesantren in Java have a relationship with the Pesantren Tegalsari, in addition to educating students, the symbols of Islam are carried out in the construction of mosques.